Comparison of Efficacy and Safety of Endoscopic Retrograde Cholangiopancreatography in Choledocholithiasis Patients at Different Age Groups: A Meta-Analysis - Wang, Bo; Cheng, Jie (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Endoscopic retrograde cholangiopancreatography (ERCP) is often recommended as the first choice for the treatment of choledocholithiasis in the elderly. This study aims to investigate the efficiency and safety of ERCP in choledocholithiasis patients of different age groups. Materials and Methods: Study searching was performed in the PubMed, Embase, Web of Science, and Cochrane Library databases from the inception to August 2024. The outcomes were complete stone clearance, mortality, overall complications, pancreatitis, perforation, biliary infection, bleeding, and pneumonia. Choledocholithiasis patients were divided into young (<65 years), general old (65 years $ age <80 years or 65 years $ age <90 years), and extremely old (#80 years or #90 years) groups. Results: Finally, 10 eligible studies were included for analysis. Compared to extremely old patients (#90 years), the complete stone clear ance was higher [odds ratio (OR) = 7.60, 95% CI: 1.89-30.57] and pneumonia was lower (OR = 0.16, 95% CI: 0.06-0.41) in general old patients (65 years $ age <90 years). Young (<65 years) patients had lower odds of mortality when compared to the age #65 years group (OR = 0.21, 95% CI: 0.17-0.27) and the age #80 years group (OR = 0.19, 95% CI: 0.15-0.24). In the comparison of 65-80 years versus #80 years, lower mortality (OR = 0.80, 95% CI: 0.65-0.98) was observed in the group of age range 65-80 years. Conclusion: Our findings suggested that extremely old patients with choledocholithiasis should cautiously choose ERCP, and postoper ative complications should be monitored in extremely old patients. Cite this article as: Wang B, Cheng J. Comparison of efficacy and safety of endoscopic retrograde cholangiopancreatography incholedocholithiasis patients at different age groups: A meta-analysis. Turk J Gastroenterol. 2025;36(6):398-407.